Vietnam 1945-1954: Revolution independence partition - Dr.Milad A.Elmagrahi (مجلة كلية الاداب, 2022)
For two thousand years, the Vietnamese have had to resist many foreign aggressions; each time, all energies have had to be mobilized. With their resistance and their love of their country, the Vietnamese gradually formed the Vietnamese nation with its own language, its distinguished culture, basically a history whose main characteristic remains stubbor resistance to all aggressors. Chinese, French, American- no matter how powerful they are. The Vietnamese resistance to the French colonialists, and then to the American imperialists continues, indeed, a tradition that started as carly as the first century A. D. with the Trung Sistors This essay will deal, briefly, with the Vietnamese resistance to the French after their return to Vietnam in 1945, and the Vietnamese struggle for independence. However, it is the August 1945 revolution and the partition of the country in 1954 that count here. An attempt to discuss and weigh the following important questions will be made: what problems did the August 1945 revolution face? How were they solved? Why did the French withdraw? If the partition of Vietnam was not inevitable, then why and how did it occur? Was it caused by